Narrating the coronavirus crisis: state talk and state silence in the UK. (31st May 2022) - Sim, Joe; Tombs, Steve
Abstract : This article is concerned with critically analysing the state's role in socially constructing the dominant narrative around COVID-19. It focuses on how the state's 'truth' about the virus in general, and deaths in particular, has been generated through a number of social practices which facilitate the dissemination of this 'truth' while silencing alternative, more critical, narratives concerning the management of the virus. The paper also considers the question of responsibility. By 2021, the UK's death rate was the third highest in the world. Given the state's relentless attempt to shift responsibility onto those breaking the lockdown rules and away from the often-lamentable decisions made by government Ministers and their advisors, who should be held to account for these preventable deaths was, and remains, a key question. This issue is addressed in the last part of the paper.